2008
DOI: 10.1017/s0142716408080296
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of tense in English: Distinguishing child second language from first language and specific language impairment

Abstract: This study reports on a comparison of the use and knowledge of tense-marking morphemes in English by first language (L1), second language (L2) and specifically language-impaired (SLI) children. The objective of our research was to ascertain whether the L2 children's tense acquisition patterns were similar or dissimilar to those of the L1 and SLI groups, and whether they would fit an (Extended) Optional Infinitive profile, or an L2-based profile, e.g., the Missing Surface Inflection Hypothesis. Results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
142
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(158 citation statements)
references
References 47 publications
13
142
2
1
Order By: Relevance
“…This potential overlap of SLI and L2 features in SLI might have influenced the results on similarities between SLI and cL2. Such similarities have been reported by Håkansson & Nettelbladt (1996), Paradis & Crago (2000), Håkansson (2001Håkansson ( , 2003, Grüter (2005), Paradis et al (2008) 2 and Orgassa & Weerman (2008). In some of these studies, the authors briefly address the question of age and maturation (Crago & Paradis 2003, Orgassa & Weerman 2008 3 ), and Håkansson (2001) proposes "a common denominator for grammatical problems in L2 children and children with SLI" (Hå-kansson 2001: 96).…”
Section: Critical Periods and Language Impairmentssupporting
confidence: 85%
See 1 more Smart Citation
“…This potential overlap of SLI and L2 features in SLI might have influenced the results on similarities between SLI and cL2. Such similarities have been reported by Håkansson & Nettelbladt (1996), Paradis & Crago (2000), Håkansson (2001Håkansson ( , 2003, Grüter (2005), Paradis et al (2008) 2 and Orgassa & Weerman (2008). In some of these studies, the authors briefly address the question of age and maturation (Crago & Paradis 2003, Orgassa & Weerman 2008 3 ), and Håkansson (2001) proposes "a common denominator for grammatical problems in L2 children and children with SLI" (Hå-kansson 2001: 96).…”
Section: Critical Periods and Language Impairmentssupporting
confidence: 85%
“…German is a V2 language with OV, with the finite verb rising to the C position in all matrix clauses, resulting in V2 2. In contrast to the earlier studies comparing SLI and cL2, Crago & Paradis (2003) and Paradis et al (2008) concentrate especially on crucial differences between these two acquisition types. Such differences indeed exist in addition to striking similarities.…”
Section: Critical Periods and Language Impairmentsmentioning
confidence: 72%
“…This corpus contains language samples from English L2 children and adult native speakers of English, all living in the Edmonton area. These language samples have been collected as part of several studies over 8 years conducted by the second author (e.g., Golberg, Paradis, & Crago, 2008;Paradis, 2008;Paradis et al, 2008;Zdorenko & Paradis, 2008. The samples were collected in a naturalistic setting and can be considered representative of the input of English L2 children in Edmonton.…”
Section: Methodsmentioning
confidence: 99%
“…Because speech-language pathologists in North America often work with children who are learning English as a second language (L2; Goldstein, 2004;Gutiérrez-Clellen, 1996;Jacobson & Schwartz, 2005), increasing our understanding of how TD children and children with LI acquire tense inflection when English is their L2 could be relevant to clinical practice. On the one hand, research comparing L2-TD children to their monolingual peers with LI has shown overlap in their difficulties with tense-marking morphology in English, suggesting that use of tense morphology might not differentiate between affected and unaffected children among L2 learners (Paradis, Rice, Crago, & Marquis, 2008). On the other hand, research comparing the use of tense morphology by English L2 learners with and without LI suggests that accuracy with tense has the potential to be a clinical marker in L2 English (Jacobson & Schwartz, 2005;Paradis, 2008).…”
mentioning
confidence: 99%
“…Jiang (2004) found that during sentence processing, Chinese learners of English tended to focus on the plurality of the subject rather than the verb, suggesting that their morphological knowledge is not part of their L2 competence. Some studies (Ellis & Sagarra, 2010;Haznedar, 2001;Ionin & Wexler, 2002;Paradis, Rice, Crago, & Marquis, 2008) explored the learning difficulty from the perspective of cognitive psychology and argued that earlier learned language cues (i.e., the plural form of the subject) blocked the acquisition of later experienced ones (i.e., the less salient verb morphology). Wang (2011) proposed that the high frequency of inflectional errors might be due to the deficiency of language experience and stimulus to trigger the already-known rules in the representation of learners' knowledge.…”
Section: Studies On L2 Acquisition Of the Third Person Singular Formmentioning
confidence: 99%